1987
DOI: 10.1079/bjn19870009
|View full text |Cite
|
Sign up to set email alerts
|

The use of monensin or formaldehyde to control the digestion of the nitrogenous constituents of perennial ryegrass (Lolium perenne cv. Melle) and white clover (Trifolium repens cv. Blanca) in the rumen of cattle

Abstract: 1. Pure swards of perennial ryegrass (Lolium perenne cv. Melle) and white clover (Trifolium repens cv. Blanca)were harvested daily as primary growth (grass in May, clover in June) or regrowths (clover only in July) and offered, in the long form, to growing cattle at a feeding rate of 22 g dry matter/kg live weight. With each forage, two treatments were compared with the untreated forage (C): monensin (100 g active ingredient/kg, 250 mg/d) addition to the rumen (treatment M) or formaldehyde (30 g/kg crude prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…After 70 DAP, A. cruentus (Zimbabwe) had greater average UIP (36%) than the UIPs reported for alfalfa (Merchen and Satter, 1983; Charmley and Veira, 1990) and perennial ryegrass (Rooke et al, 1983; Rooke et al, 1987; Dawson et al, 1988). The percentage of UIP reported for white clover ( Trifolium repens ) (Beever et al, 1987) is also lower than that of A. cruentus (Zimbabwe) and A. cruentus (Rwanda) after 70 DAP. The comparison across species should be noted with some caution since these species were evaluated under different environmental conditions.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…After 70 DAP, A. cruentus (Zimbabwe) had greater average UIP (36%) than the UIPs reported for alfalfa (Merchen and Satter, 1983; Charmley and Veira, 1990) and perennial ryegrass (Rooke et al, 1983; Rooke et al, 1987; Dawson et al, 1988). The percentage of UIP reported for white clover ( Trifolium repens ) (Beever et al, 1987) is also lower than that of A. cruentus (Zimbabwe) and A. cruentus (Rwanda) after 70 DAP. The comparison across species should be noted with some caution since these species were evaluated under different environmental conditions.…”
Section: Resultsmentioning
confidence: 86%
“…The concentration of UIP in different forages has been reported (Merchen and Satter, 1983; Mathers and Miller, 1981; Rooke et al, 1983; Charmley and Veira, 1990; Glenn et al, 1989; Beever et al, 1987). Mitchell et al (1997) reported UIP for switchgrass ( Panicum virgatum L.) and smooth bromegrass ( Bromus inermis L.) as 230 to 310 and 110 to 180 g kg −1 of total crude protein, respectively, and that warm‐season grasses generally had greater UIP because of their C 4 anatomy.…”
mentioning
confidence: 99%
“…Poos et al (24) reported that monensin caused an increased flow of amino acid nitrogen to the lower gut, but in other studies the flow of nonammonia nitrogen was only marginally increased (2). In some cases, the increased flow of plant amino acids was countered by a decreased flow of microbial protein (24).…”
Section: Discussionmentioning
confidence: 98%
“…NAN passage to the duodenum on high quality forage diets is I to 2 glMI ME intake (Beever et al 1987). This figure is usually lower with high energy (feedlot) diets, because of reduced ruminal dilution rate (Owens et al, 1984).…”
Section: Discussionmentioning
confidence: 99%